Challenges in predicting new firm performance - Cooper, Arnold C. (Journal of Business Venturing, 1993)
Research examining predictors of new firm performance is clearly of interest to entrepreneurs and to those who provide advice and funds for their ventures. A growing body of research has examined the influence upon performance of such variables as entrepreneurs' characteristics, processes of founding, venture attributes, and environmental characteristics. However, considered as a whole, this research has shown mixed results and limited findings to date. This paper considers some of the challenges that arise in attempting to predict new firm performance. A key factor is the heavy dependence of new ventures upon environmental developments, many of which may be very difficult to predict. All firms are impacted by the environment, but new ventures have a concentration of risk upon a few products or services, narrow markets, and a few key resources. Thus, well-conceived ventures can fail because of unforeseen environmental shocks and the lack of “deep pockets” to ride out hard times. These same factors can cause new firm performance to swing widely, confounding attempts to identify predictors of good or poor performance. There are also challenges because many entrepreneurs pursue personal goals, some of which are noneconomic in nature. Thus, decisions about whether to found ventures, about how vigorously to grow them, or about whether or not to close down marginal businesses are all influenced by the personal values of entrepreneurs. The diversity of ventures, encompassing firms that differ greatly in scale and potential, complicates the task of determining predictors of performance. It may be that the influence of a particular variable, such as management experience, varies by type of venture. Previous research has also used a variety of performance measures, making comparisons across studies more difficult. Little has been done to determine whether the factors that enhance one measure of performance, such as survival, are the same as those that lead to others, such as growth or profitability. Previous research has been hampered by inadequate theoretical frameworks and, in some cases, by inappropriate methods of analysis. In addition, past research often could have been characterized by a tendency to examine variables that were easy to study, rather than those that were important. Despite limited success to date, we should not forsake research on predictors of new venture performance. The challenges discussed probably put limits on our ability to predict performance of individual ventures. However, the field of study is young and there is much that can be done to add to our understanding. The paper then develops recommendations for future research, noting that each of the challenges considered raises specific research opportunities.